ARBUSCULAR MYCORRHIZA FUNGI AS AN INDICATOR OF SOIL FERTILITY - Syibli, Muhammad Akhid; Muhibuddin, Anton; Djauhari, Syamsuddin (AGRIVITA Journal of Agricultural Science, 2013)
Arbuscular mycorrhizal fungi (AMF) are ubiquitous organism that forms association with the root of most terrestrial plants. AMF association also influence soil fertility through the enhancement of chemical, biological and physical content. In this study, we enumerated AMF spores from rhizosphere of Tithonia difersivolia as an indicator of soil fertility. The results showed that the most fertile soil had the highest AMF spores density. This research has confirmed that AMF has high interaction with organic carbon, organic matter, total phosphorus, cation exchange capacity, water level, soil fungi and soil bacteria. Partial regression analysis revealed the mathematic equation for their interaction. This equation used the abundant of AMF spores as an indicator for chemical, biological and physical fertility of the soil.                 Keywords: Arbuscular mycorrhiza fungi (AMF), indicator, soil fertility, Tithonia difersivolia